Pemberdayaan Masyarakat Melalui BUMDes di desa Janji Manahan Sil Kecamatan Dolok Kabupaten Padang Lawas Utara. - Ritonga, Maulidan Taufik (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research examines community empowerment through the Village Owned Enterprise program which is being developed in Janji Silangge Village, Dolok District, North Padang Lawas Regency. This type of research is field research with a Juridical Empirical approach. The primary data sources are the Village Head, Village Officials, Community. Secondary data sources are books, data and documents. Data collection techniques used Observation, Interview and Documentation methods. The data analysis technique is qualitative and descriptive. The results of this study explain that the development process in which the people of Janji Manahan Silangge Village, Dolok District, North Padang Lawas Regency took the initiative to start a process of social activities to improve their own situation and condition. on the edge of tourist attractions. Village-owned enterprise programs, namely water tourism, stalls, lubukban, the process of profit sharing from the village-owned enterprise program of 20%, The supporting factors in the development program for village-owned enterprises are appropriate and running well because Janjimanahan village Silangge is between two regencies, namely Labuhan Batu Selatan and Labuhan Batu regencies, before the dam was made into a tourist spot, this dam has been around for a long time and before this tourist spot existed, this dam was often visited by local and foreign people to visit . The inhibiting factors for the BUM Desa program in Janjimanahan Village, Dolok District, North Padang Lawas Regency, where the village community is envious in running this program and human resources are far different from those in urban areas.